2012
DOI: 10.1111/acel.12032
|View full text |Cite
|
Sign up to set email alerts
|

Stress profiling of longevity mutants identifies Afg3 as a mitochondrial determinant of cytoplasmic mRNA translation and aging

Abstract: Summary While environmental stress likely plays a significant role in promoting aging, the relationship remains poorly understood. In order to characterize this interaction in a more comprehensive manner, we examined the stress response profiles for 46 long-lived yeast mutant strains across four different stress conditions (oxidative, ER, DNA damage, and thermal), grouping genes based on their associated stress response profiles. Unexpectedly, cells lacking the mitochondrial AAA protease gene AFG3 clustered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…Yeast mutants deficient for ribosomal large subunits or with less cytosolic mRNA were found to be more resistant to Tm, which may be due to lower protein synthesis overall (58,59). In agreement with this notion, we found that limiting leucine, uracil, and histidine slightly improved tolerance to Tm.…”
Section: Discussionsupporting
confidence: 85%
“…Yeast mutants deficient for ribosomal large subunits or with less cytosolic mRNA were found to be more resistant to Tm, which may be due to lower protein synthesis overall (58,59). In agreement with this notion, we found that limiting leucine, uracil, and histidine slightly improved tolerance to Tm.…”
Section: Discussionsupporting
confidence: 85%
“…In a paradoxical way, in yeast (Delaney et al., 2013), worms (Dillin et al., 2002), flies (Owusu‐Ansah, Song & Perrimon, 2013), and mice (Liu et al., 2005), suppression of mitochondrial ETC function increases lifespan (Dell'agnello et al., 2007; Durieux, Wolff & Dillin, 2011). While counterintuitive, these findings are supported by reports demonstrating that upregulation of mitochondrial stress response contributes to enhanced longevity in the long‐lived mitochondrial mutants (Durieux et al., 2011; Kirchman, Kim, Lai & Jazwinski, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial unfolded protein response and the role of CLPP seem to be conserved in mammals (Benedetti et al., 2006; Zhao et al., 2002), where activation of JNK/c‐JUN pathway leads to the expression of transcription factor C/EBP‐homologous protein (CHOP), which, together with C/EBP, mediates the transcription of mtUPR genes (reviewed in Hill & Van Remmen, 2014). It is important that, in addition to inducing transcription of over 400 genes, mtUPR in yeast, C. elegans , and mammals are associated with phosphorylation of eukaryotic initiation factor 2 alpha (eIF2a) by general control nonderepressible 2 (GCN2), resulting in global suppression of translation while mRNAs that contain upstream open reading frames (uORFs) are preferentially translated (Delaney et al., 2013; Rath et al., 2012). Transcriptional activation of mtUPR genes and translational suppression seem to be mediated by two parallel mechanisms, both requiring CLPP (Aldridge et al., 2007; Benedetti et al., 2006; Haynes et al., 2007; Zhao et al., 2002) and reviewed in (Jensen & Jasper, 2014; Schulz & Haynes, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that an increase in eukaryotic translation initiation factor 2 alpha (eIF2α) phosphorylation occurs in response to mitochondrial stress in both worms and mammals [6, 6365] resulting in the attenuation of global protein synthesis while preferentially translating those mRNAs that contain upstream open reading frames (uORFs) [66]. Four eIF2α kinases exist, but in yeast, C. elegans , and mammals, the kinase general control non-derepressible 2 (GCN2) appears to contribute the most to the induced eIF2α phosphorylation that occurs during mitochondrial stress [6, 63, 64, 67] (Figure 2). However PKR, an eIF2α kinase that responds to double stranded RNA, has also been shown to be required for eIF2α phosphorylation during mitochondrial stress in the mouse intestine suggesting mitochondrial dysfunction activates multiple eIF2α kinases [65].…”
Section: Regulation Of the Uprmtmentioning
confidence: 99%